(untitled) (Applied Biological Research, 2025)
Syzygium cumini L., belonging to the family Myrtaceae, is an edible fruit well known for its nutritional values and several beneficial effects on human health. The present study aimed to isolate polysaccharides from S. cumini seeds and assess their biological activities. The S. cumini polysaccharide (SCP) was extracted using a hot water extraction process followed by ethanol precipitation and subjected to physiochemical characterization. UV-visible spectrum analysis confirmed the extract to be a protein-free polysaccharide, while Fourier-transform infrared spectroscopy (FTIR) revealed its functional groups. Scanning electron microscopy (SEM) images depicted a smooth and non-porous surface morphology, while thin-layer chromatography (TLC) indicated the presence of monosaccharide constituents in crude polysaccharide hydrolysates. SCP exhibited high total antioxidant capacity and strong radical scavenging activity in DPPH, ABTS, and FRAP assays. Additionally, SCP effectively inhibited α-amylase and α-glucosidase, enzymes involved in carbohydrate metabolism. Furthermore, SCP enhanced the intracellular killing activity of stimulated neutrophils and increased neutrophil candidacidal activity in a dose-dependent manner. These findings suggest that polysaccharides isolated from S. cumini seeds possess significant antioxidant, antidiabetic, and immunostimulatory properties.